Scientific Freedom - Giordano, Simona; Coggon, John; Cappato, Marco (Science Ethics and Society, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Scientific Freedom is the first comprehensive collection covering both the state of scientific progress and the ethics, law and history of scientific research. The book gives readers a fascinating range of perspectives on matters of scientific research that directly affect all of us. Examining the ethical, legal, social, economic and political issues surrounding freedom of scientific research, the book evaluates ways in which national and international policies can impact upon individuals' access to potentially life-saving treatment, cures and technologies, and can therefore affect human life and death. With contributions from Nobel Laureates, representatives of patients' associations, scientists, scholars and politicians, this book provides a concise and comprehensive view of the limitations and dangers facing the future of innovation and scientific progress.